The Omnipresence of Television and the Ascendancy of Surveillance/Sousveillance in Ray Bradbury’s Fahrenheit 451 - Hassan Abootalebi (kata, 2017)
This paper is an attempt to analyze Ray Bradbury’s Fahrenheit 451(1953) under the light of Jean Baudrillard’s notions on the media and the influences it exerts on people’s daily lives, and with an eye to Michel Foucault’s surveillance as well. The title-mentioned work, it is suggested, portrays a representative sample of a culture where different fields including books, education, and history fall under the influence of the media. Bradbury presents a society in which its inhabitants are bombarded with excessive data transmitted through television most of which is detrimental and not reliable. It is concluded that the presented culture in the novel is a microcosm of contemporary societies where authorities keep their subjects under control, engendering an atmosphere of anxiety, trepidation and apprehension for subversive forces and therefore preclude any disturbance on the part of them